ANALISIS PENGARUH PRODUK, MEREK DAN HARGA TERHADAP STRATEGI PROMOSI DAN DAMPAKNYA TERHADAP KEPUASAN PEMBELIAN PRODUK KECAP MANIS BANGO - Miyv Fayzhall dan Santo Suwandi (Jurnal Manajemen FE-UB, 2016)
Based on the test results using path analysis is known that the product, brand, and price together have a significant positive effect on promotion strategy.Afterwards, it can be seen that the products and promotional strategies proved to have a significant positive effect on purchasing decisions. While the price proved to have no significant positive effect on purchasing decisions.The test results using path analysis proves that the Product, price and promotion strategy proved together to positively and significantly influence the purchasing decision and not all variables are accepted because based on the coefficient test of sub-structure 2 lane only the coefficient of the price path to purchase decision that is not statistically significant. Thus the findings of this analysis provide information that Promotional Products and Strategies have a significant effect on purchasing decisions. Keywords: Product, Brand, Price, Promotion Strategy & Purchase Decision.